The Laboratory Preparedness and Tasks in Disaster Situations - Bolayırlı, İ. Murat; Kucur, Mine; Konukoğlu, Dildar (Cerrahpaşa Medical Journal, 2023)
Emergencies and disasters require prompt and adequate response, and assistance needs to be provided and monitored until normal services resume. To meet these demands, contingency plans and preparedness are essential. Clinical laboratories should have a comprehensive disaster plan for all types of disaster situations. This plan should provide a high level of comprehensive security control for the laboratory, personnel, and equipment and include processes to ensure the continuation of health care in the laboratory. In order to respond quickly and adequately to an emergency or disaster, each country should establish a national emergency plan and emergency preparedness and response mechanisms in the health sector. Clinical laboratories should also be included in plans suitable for this emergency preparedness. In the event of a disaster, the service processes of clinical laboratories may also be disrupted, and at the same time, personnel, equipment, material, and facility problems may occur, and/or a new laboratory may be established. In this article, the scope of disaster preparedness and disaster plans in clinical laboratories and the basic stages of the processes are summarized. Cite this article as: Bolayırlı İM, Kucur M, Konukoğlu D. The laboratory preparedness and tasks in disaster situations. Cerrahpaşa Med J 2023;47(S1):75-77.